Multi-Project Management (Review and Challenges in Rockwell Automation Southeast Asia) - KIM, Kun (2009)
The aim of this Management Project is to analyze the current Project division of an American Multinational company’s subsidiary in Southeast Asia (Rockwell Automation Southeast Asia Pte Ltd) from the academic point of view and revise what the obstacles and issues are for the multi-project management and operation management. This report will analyze the current issues of the company based on the company’s goal. And using project management and operation management theories along other organization’s project execution model, the report will suggest the optimal organizational (or departmental) model and procedures to achieve its ultimate goal.